PENINGKATKAN KOMPETENSI KEPRIBADIAN GURU DALAM MENGEMBANGKAN AKHLAK MULIA PESERTA DIDIK MELALUI PENANAMAN NILAI-NILAI KARAKTER BUDAYA JAWA - Nurkhan, Nurkhan (Jurnal Counsellia, 2015)
Objective is to be achieved in this study was to determine the success of planting values-based character of Javanese culture in improving personal competence of teachers, research was conducted in Dabin Sudirman is in SD 1 Bulungcangkring. To determine the success of the study, the researchers gave the pretest and reflection, reflection in cycle 1 and 2. The purpose of the pretest was to determine the initial condition of personal competence of teachers, while the reflection 1 and 2 is intended to determine the success of the action, whether the action is implemented there is increasing? what does not. in addition to validating the results of the study, researchers using observation data and observations that have been analyzed, the data will be used for the development of more lanjut.Dari data analysis proved that there is an increase in the average score rose 24.9 points from the value of the pretest or 12 , 44%. Keywords : Javanese culture, character, attitude, personality